1990
DOI: 10.1038/jcbfm.1990.140
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of Intracranial Pathophysiological Changes following Experimental Subarachnoid Haemorrhage in the Rat

Abstract: Summary:The rat subarachnoid haemorrhage (SAH) model was further studied to establish the precise time course of the globally reduced CBF that follows and to ascertain whether temporally related changes in cerebral perfusion pressure (CPP) and intracranial pressure (lCP) take place. Parallel ultrastructural studies were per formed upon cerebral arteries and their adjacent perivas cular subarachnoid spaces. SAH was induced by a single intracisternal injection of autologous arterial blood. Serial measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
93
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(106 citation statements)
references
References 72 publications
13
93
0
Order By: Relevance
“…The fall in perfusion in the cerebral cortex after SAH was confirmed by measuring a similar fall in the supply rate of FRBCs in capillaries on the cortical surface with videomicroscopy. The time course and magnitude of the changes in cerebral blood flow in the present study are similar to those reported by Jackowski et al (22), who found that cerebral blood flow measured with hydrogen clearance fell to 57 Ϯ 11% of control for up to 3 h after injection of blood into the cisterna magna of rats. In their study, rCBF remained reduced at 85 Ϯ 15% of control at 24 h and returned to control 48 h after induction of SAH.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The fall in perfusion in the cerebral cortex after SAH was confirmed by measuring a similar fall in the supply rate of FRBCs in capillaries on the cortical surface with videomicroscopy. The time course and magnitude of the changes in cerebral blood flow in the present study are similar to those reported by Jackowski et al (22), who found that cerebral blood flow measured with hydrogen clearance fell to 57 Ϯ 11% of control for up to 3 h after injection of blood into the cisterna magna of rats. In their study, rCBF remained reduced at 85 Ϯ 15% of control at 24 h and returned to control 48 h after induction of SAH.…”
Section: Discussionsupporting
confidence: 91%
“…Despite intensive investigation, the factors that produce the acute fall in cerebral blood flow after SAH are still uncertain (4,22,28,36,44). Endothelin (ET) levels increase after SAH (23,35), and the acute fall in cerebral blood flow after SAH in rats is attenuated by inhibitors of the synthesis of ET or ET receptor blockers (9).…”
mentioning
confidence: 99%
“…In experimental work, a dramatic increase in the numbers of subarachnoid macrophages was found to arise within 24 -48 h of SAH from the transformation of cells of the pia-arachnoid. This period is characterized by intense phagocytic activity, with erythrocytes, fibrin, and other debris being largely cleared (213). Moreover, the recent demonstration of COX-2 expression in choroid plexus preparations removed 3 days after SAH in what are probably epiplexus macrophages (or Kolmer cells) (214) also suggests some contribution to inflammation by macrophages bathing in the CSF.…”
Section: Studies On Immunocompetent Cellsmentioning
confidence: 99%
“…This is because soon after the bleeding an important vasoconstriction occurs in cerebral arteries, perhaps as a mechanism of defence against bleeding. Following this vasoconstriction, a delayed vasospasm appears, usually more than 48 h after that, as pioneering studies in rats revealed [29,30]. Many theories have tried to explain how this delayed vasospasm occurs, among them an alteration in the production of nitric oxide (NO) by the vascular endothelium [31], hence impairing the vasodilatory activity of this gas and the hemodynamic cerebral autoregulation.…”
Section: Discussionmentioning
confidence: 99%